Broad-spectrum resistance mechanism of serine protease Sp1 in Bacillus licheniformis W10 via dual comparative transcriptome analysis - Yang, Lina; Yan, Chun; Peng, Shuai; Chen, Lili; Guo, Junjie; Lu, Yihe; Li, Lianwei; Ji, Zhaolin (Frontiers in Microbiology, 2022)
Antagonistic microorganisms are considered to be the most promising biological controls for plant disease. However, they are still not as popular as chemical pesticides due to complex environmental factors in the field. It is urgent to exploit their potential genetic characteristics and excellent properties to develop biopesticides with antimicrobial substances as the main components. Here, the serine protease Sp1 isolated from the Bacillus licheniformis W10 strain was confirmed to have a broad antifungal and antibacterial spectrum. Sp1 treatment significantly inhibited fungal vegetative growth and damaged the structure of hyphae, in accordance with that caused by W10 strain. Furthermore, Sp1 could activate the systemic resistance of peach twigs, fruits and tobacco. Dual comparative transcriptome analysis uncovered how Sp1 resisted the plant pathogenic fungus Phomopsis amygdali and the potential molecular resistance mechanisms of tobacco. In PSp1 vs. P. amygdali, RNA-seq identified 150 differentially expressed genes (DEGs) that were upregulated and 209 DEGs that were downregulated. Further analysis found that Sp1 might act on the energy supply and cell wall structure to inhibit the development of P. amygdali. In TSp1 vs. Xanthi tobacco, RNA-seq identified that 5937 DEGs were upregulated and 2929 DEGs were downregulated. DEGs were enriched in the metabolic biosynthesis pathways of secondary metabolites, plant hormone signal transduction, plant-pathogen interactions, and MAPK signalling pathway-plant and further found that the genes of SA and JA signalling pathways were highly expressed and the contents of SA and JA increased significantly, suggesting that systemic resistance induced by Sp1 shares features of SAR and ISR. In addition, Sp1 might induce the plant defence responses of tobacco. This study provides insights into the broad-spectrum resistance molecular mechanism of Sp1, which could be used as a potential biocontrol product.